Respostas
respondido por:
23
função: f(x)=2x²+3x-5
f(0)= 2.0²+3.0-5
f(0)= 0+0-5
f(0)= -5
f(-1)= 2.(-1)²+3.(-1)²-5
f(-1)= 2+3-5
f(-1)= 0
f(2)= 2.2²+3.2²-5
f(2)= 2.4+3.4-5
f(2)= 8+12-5
f(2)= 15
f(3/2)= 2.(3/2)²+3.(3/2)²-5
f(3/2)= 2.9/4+3.9/4-5
f(3/2)= 18/4+27/4-5
f(3/2)= 45/4-5
f(3/2)= 45-20/4
f(3/2)= 25/4
f(0)= 2.0²+3.0-5
f(0)= 0+0-5
f(0)= -5
f(-1)= 2.(-1)²+3.(-1)²-5
f(-1)= 2+3-5
f(-1)= 0
f(2)= 2.2²+3.2²-5
f(2)= 2.4+3.4-5
f(2)= 8+12-5
f(2)= 15
f(3/2)= 2.(3/2)²+3.(3/2)²-5
f(3/2)= 2.9/4+3.9/4-5
f(3/2)= 18/4+27/4-5
f(3/2)= 45/4-5
f(3/2)= 45-20/4
f(3/2)= 25/4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás